Frontotemporal Dementia Knowledge Scale: Development and Preliminary Psychometric Properties. (January 2020) - Wynn, Matthew J.; Carpenter, Brian D.
Abstract : Objective: Frontotemporal dementia (FTD) accounts for ∼10% of dementia cases and is the most common cause of early-onset dementia. However, no well-validated instrument currently exists to measure knowledge about FTD. In this study, we used systematic scale development procedures to create a scale to measure knowledge of FTD based on a contemporary understanding of the disease. Methods: Standard scale development methods were used to create items and evaluate their psychometric properties. A total of 72 health care professionals and 102 caregivers of people with FTD responded to items measuring FTD knowledge, general dementia knowledge, crystallized intelligence, experience with FTD, and demographic information. Results: The Frontotemporal Dementia Knowledge Scale (FTDKS) contains 18 items that cover key, basic knowledge about FTD in the domains of risk factors, symptoms, course, caregiving, and treatment. The scale uses a 4-point True/False format with a Don't Know option and takes ∼5 minutes to complete. In the current sample the FTDKS had good psychometric properties in terms of reliability and validity. Implications: The FTDKS can be used with health care professionals and caregivers of people with FTD to assess their knowledge about the disease. The scale may be useful to evaluate knowledge in clinical care and educational program contexts.